Evaluating life cycle environmental impacts of coal fly ash utilization in embankment versus sand and landfilling. (20th January 2023) - Curpen, Sarah; Teutsch, Nadya; Kovler, Konstantin; Spatari, Sabrina
Abstract: Coal fly ash (CFA) disposal is controversial because constituents of potential concern such as heavy metals in the ash can be released to the ground and reach aquifers, which poses risks to communities and the environment. Whereas thoughtful utilization of CFA may result in economic and environmental benefits. Geotechnical use of CFA as fill material in embankments could be economically competitive while reducing environmental impact. However, CFA must compete with low-cost alternatives like sand, which do not need to adhere to stringent environmental regulations and have not been evaluated against CFA previously in life cycle assessment (LCA) studies. Therefore, this work aims to evaluate the environmental effects of using CFA versus sand through LCA. Leaching experiments were carried out to create mass balance emission profiles of heavy metals from the embankment. Those emissions were integrated into a complete life cycle inventory for use of the material. Results show a net reduction in the impact categories for CFA re-used in embankments compared to landfilled. The effects of sand impacts were mostly attributed to the sand mining process. The ultimate environmental impacts from utilizing CFA as fill material in an embankment were a result of truck emissions from transporting CFA from power stations to point of utilization, diesel production and its consumption during truck transport, and leachate emissions. The breakeven distance for transporting CFA as opposed to sand was evaluated as 115 km. Graphical abstract: Image 1 Highlights: Comparison of coal fly ash and soil fill use in embankments with LCA. Net reduction in impact categories for higher lime content coal fly ash. Leaching contributes significantly to freshwater ecotoxicity life cycle impact. Arsenic contributes to freshwater ecotoxicity. Chromium contributes to cancer and non-cancer human toxicity impacts.